ANATOMIA QUANTITATIVA DA FOLHA DE CEVADA (Hordeum vulgare L.) SUBMETIDA A DÉFICIT HÃDRICO - Domingues, Márcio C. S.; Urchei, Mário Artemio; Rodella, Roberto Antonio (REVISTA DE AGRICULTURA, 2015)
ANATOMIA QUANTITATIVA DA FOLHA DE CEVADA (Hordeum vulgare L.) SUBMETIDA A DÉFICIT HÃDRICO